UNDERHAND PURCHASE AGREEMENT IMPLEMENTATION OF LAND AND BUILDING PURCHASING FROM DEVELOPER FROM PERSPEKTIF OF CONSUMER PROTECTION LAW - Wahyu Amzari; Damrah Mamang; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2022)
This study aims to analyze the sale and purchase of land with PPJB under the hand, in which the application of the principle of clear and cash sale and purchase transactions cannot be carried out. In practice in the field, not all transactions can be carried out by applying the principle of light and cash due to several factors, for example because the payment has not been paid in installments, the certificate is still in the process of splitting or other processes, not being able to pay taxes, or other factors. The focus of the researcher is to find out what factors cause the occurrence of PPJB under the hands of the sale and purchase of land and buildings from the developer, the legal consequences and the concept of legal protection for consumers, the legal research method is descriptive (normative law). empirical research, namely by conducting a brief interview with one of the legal officials at PT. Prima Sehati, domiciled in Jakarta (developer) and a consumer. The factors that led to the implementation of PPJB under the hands were, among others, because payments were made in stages, either in cash in stages or with bank facilities, the certificate was still in the process of splitting, merging and decreasing rights, PBG was still in the process at the relevant agency and the last reason was because it was practical and economical. cost. PPJB made under the hands results in being null and void because it violates the objective conditions in an agreement, so that the PPJB under the hand is considered to have never existed from the start, so as a result of the law the party who has received the achievement is obliged to return it to the party who has fulfilled the achievement, this is aims to return the situation to its original state, the concept of consumer protection to resolve disputes/defaults can be done through the courts, namely through courts that are in the general court environment. Settlement of disputes/defaults outside the court, namely through the Consumer Dispute Settlement Agency (BPSK) at level II areas or through other dispute resolution institutions in order to obtain a fair agreement.